Éléments d'une sociolinguistique critique - Heller, Monica (Langages, 2023)
This second edition updates a text which laid the foundations of the field of critical ethnographic sociolinguistics, and which has become an essential reference and important teaching tool. The book lays the foundation of this approach through a longue durée ethnography of the practices, discourses and ideologies of language and nation in francophone Canada. The new edition provides an update of the development of the ethnographic sites discussed, as well as on the theoretical, methodological, political and ethical aspects of the approach.